PENGIRIMAN E-MAIL SPAM SEBAGAI KEJAHATAN CYBER DI INDONESIA - Putra, Eka Nugraha (Jurnal Cakrawala Hukum, 2016)
The Internet is part of the development of technology, where the internet provides many impacts, both positive and negative. Currently, privacy issues on the internet have also become a complicated legal issue, this is due to quite a number of privacy-related issues, but not all countries in the world manage privacy issues on the internet. As a means of communicating the Internet has introduced e-mail that provides convenience and practicality. But in its development e-mail has an adverse impact on its users in the form of e-mail spam. In terms of its actions, sending spam e-mail is quite a disadvantage, even violate the privacy. Some countries have also set it to one type of cybercrime (cybercrime). This research will discuss e-mail spam in Indonesia, how the legislation in Indonesia see the action of this spam e-mail, is there any possibility of spam e-mail is criminalized as a cybercrime. The research will also look at how spam e-mails violate privacy and review and analyze internet privacy settings in Indonesia in relation to the criminalization of spam email.